Problems related to the employment of thin uranium films as neutron dosimeters - Bigazzi, G.; Hadler, J. C.; Iunes, P. J.; Khouri, M. C.; Navia, L. M S; Osorio, A. M. [UNESP]; Paulo, S. R.; Zúñiga, A. (Elsevier, 1995)
Thin uranium films built on muscovite mica basis and obsidian samples having known ages were irradiated with thermal neutrons at the IPEN/CNEN reactor, São Paulo. Comparing thin film performance with the obsidian one, it was observed that the latter feel a greater neutron fluence. Nominal fluences at the used facility are in agreement with the results obtained analysing the obsidian samples. A probable hypothesis to explain this disagreement, namely, the uranium loss from the thin films, was ruled out. © 1995.
Keywords: Fission track dating; neutron dosimetry; uranium thin films